MANAJEMEN HAJI DAN UMRAH DALAM PEMETAAN BIBLIOMETRIK - Mansyur, Abdurrahman; Hudaya, Nurul (Multazam : Jurnal Manajemen Haji dan Umrah, 2023)
This research aims to analyze research trends in the field of Hajj and Umrah management from researchers around the world. Through bibliometric analysis, this research provides an overview of research maps formed from keywords and important issues analyzed using the VOSviewer application. Data was obtained from the Dimensions.ai database, with the search keyword "Hajj and Umrah Management". The research results found that research on Hajj and Umrah management has increased every year. Writers from Indonesia and Arabic are the major contributors in this studies. The results of the cluster analysis found six theme clusters, cluster 1 discussed the theme of crowd management strategies. Cluster 2, regarding special service aspects for groups of Hajj and Umrah pilgrims. Cluster 3 shows a close relationship between the themes of the Ministry of Religion, Policy and Transparency. Cluster 4 underlines the issue of customer satisfaction, the role of related institutions and Umrah services in Indonesia. Meanwhile, cluster 5 groups issues regarding the application of technology, applications and information systems in Hajj management. And cluster 6, reflects the relationship between the COVID-19 Pandemic and Hajj and Umrah Management.